ДІАГНОСТИЧНА ЦІННІСТЬ ДОСЛІДЖЕННЯ ТРАНСФЕРИНУ НА РІЗНИХ СТАДІЯХ РОЗВИТКУ АНЕМІЇ ЗЛОЯКІСНОГО НОВОУТВОРЕННЯ У ПАЦІЄНТІВ ІЗ УРОТЕЛІАЛЬНИМ РАКОМ СЕЧОВОГО МІХУРА - Станіслав Видиборець; Дмитро Борисенко (World Science, 2019)
In clause the items of information on transport protein of iron - transferrin are stated. Its physiological role and clinical importance is shown. The content of iron in the blood whey (SZH) and index of general iron- binding ability of the whey (OZHSS) were determined by batofenantrolin method. The index of the unsaturated iron-binding ability of the whey (NZHSS) was calculated as a difference between OZHSS and SZH. The coefficient of saturation of transferrin by iron (KNTZH) was determined as correlation of maintenance of SZH to OZHSS. The contents of transferrin (TF) was determined on the index of OZHSS, ferritin (FN) by a radiometric method. Dynamics of the contents of the transferrin of the patients with anemia of malignant growth in patients with urothelial cancer of the urinary bladder. The conclusion about importance of the given parameter for laboratory diagnostics of iron deficiency condition and anemia of malignant growth is made.